The Final Frontier: The Integration of Banking and Commerce. Part 1: The Likely Outcome of Eliminating the Barrier - Larry D. Wall; Alan K. Reichert; Hsin-yu Liang (Economic Review, 2008)
The policy debate on whether to strengthen or to remove the legal barriers between banking and commerce has paid little attention to what the practical effects of removing the barriers would be. To help answer this question, this article, the first part of a two-part study, provides an overview of the potential gains of integrating banking and commerce. Economic theory, the authors note, suggests that joint corporate ownership of banks and commercial firms has several potential benefits, including economies of scale and scope, increased internal capital markets, and diversification. Commercial firms could also enjoy a significant reduction in funding costs if affiliation with a bank extended the federal safety net for banks to cover the commercial firms' liabilities. But some benefits are already available without common ownership. Moreover, common ownership may also result in some disadvantages, such as significant diseconomies of scale and scope. Actual experience provides better insight than theory can about the relative magnitudes of the benefits and costs of cross-industry combinations. U.S. experience with limited openings between banking and nonbank activities suggests that the most common combinations were banks with nonbank financial firms, relationships that were authorized by a 1999 reform act. Foreign experience and U.S. conglomerates of nonbank firms in different industries fail to provide compelling evidence for large-scale combinations of banking and commercial firms.
Keywords: G21; G34; G28; 330; banking and commerce; Bank; Handel; Bankrecht; Deregulierung; Kosten-Nutzen-Analyse; Skalenertrag; Verbundvorteil; USA